KAP survey in patients of dermatophytosis in a tertiary care hospital: a cross-sectional study - Chopra, Preeyati; Aulakh, Shayna; Goel, Seema; Chopra, Dimple (International Journal Of Community Medicine And Public Health, 2023)
Background: Dermatophytes are a group of fungi with the capacity to invade keratinized tissue. Along with etiological factors, the clinical and epidemiological patterns has shown changing trend, leading to epidemic state of dermatophytosis. This could be attributed to inadequate knowledge and substandard practices followed by patients of dermatophytosis. Methods: A cross-sectional observational survey of patients with dermatophytosis who visited the outpatient department of dermatology at a tertiary healthcare facility over a period of two months to assess knowledge, attitude and practices regarding dermatophytosis management was performed. Results: A total of two hundred and twenty-seven (227) patients were recruited in during 2-month study period. The male:female ratio was 0.82:1. Fifty two percent respondents were from a rural background. Fifteen percent of respondents had cattles as pets. Majority of the respondents preferred wearing loose clothes (79%), 89% wore cotton as the material of cloth and 35% preferred wearing closed footwear. Seventy two percent were unaware of the infective nature of disease and 84% of the treatment of this condition 11.45% were hesitant to take oral treatment for the same. More than half of the patients gave a history of self-medication, and 27% of the patients gave a history of receiving steroid injections. Conclusions: This study concluded that there is an extensive knowledge gap in this subset of the population, which lead to faulty and substandard practices, such as self-treating, steroid abuse and visiting quacks before considering registered dermatologists for treatment purposes.